Mental health variables affecting Quality of Life (QOL) among healthcare workers during the COVID-19 pandemic in Jazan City, Saudi Arabia - Alfaifi, Amal Jaber; Abdaly, Ahmed Yahia; Alallah, Sultan Musa; Zaino, Mohammad; El-Setouhy, Maged (Frontiers in Psychology, 2024)
Background: health workers directly involved in the diagnosis, treatment, and care of patients with COVID-19 are at risk of developing mental health symptoms. Objective: The study aimed to assess the quality of life (QoL) of healthcare workers at Prince Mohammed bin Nasser Tertiary Hospital in Jazan during the COVID-19 pandemic, with a focus on the relationship between QoL and stress, anxiety, and depression. pandemic. Methods: This was a cross-sectional study conducted among healthcare workers at Prince Mohammed bin Nasser Hospital in the Jazan. The study included a sample of 352 healthcare workers. Data was collected through a self-administered questionnaire pertaining to sociodemographic characteristics and the 21-item Depression Anxiety Stress Scale questionnaire, SF-36, for QoL. Descriptive statistics, frequencies, and percentages were used. A chi-squared test was performed to compare categorical data. A one-way ANOVA was performed to compare the effect of disorder variables on QoL. Multiple linear regression analyses were carried out to discern the differences between the different groups of participants in QoL measures. Results: Our results showed a poor QoL among those with a chronic disease (p = 0.002), who worked in the COVID-19 department (p = 0.030) and those who experienced the death of relatives or friends due to COVID-19 (p = 0.003). Conclusion: Healthcare workers, particularly those with chronic diseases or who had lost relatives to COVID-19, exhibited significantly lower QoL levels, especially those working directly in COVID-19 departments.